The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0004-282x20150186
|View full text |Cite|
|
Sign up to set email alerts
|

Transient ischemic attack caused by cerebral ergotism

Abstract: Association of protease inhibitors and ergotamine causing systemic ergotism is well established 1,2,3 . Cerebral ergotism is poorly reported 4,5 . We describe the case of an HIV positive 49 yo man under protease inhibitors (ritonavir) presenting with total reversible left hemiparesis after the intake of 3 g of ergotamine. After 20 minutes he was spontaneously asymptomatic. TIA was diagnosed. Parenchymal MRI was normal, cervical doppler ultrasound showed symmetric narrowing in both internal carotid arteries, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Carotid involvement is uncommon but it has been described. 5 Septicemia, as in the case reported, can increase the vasoconstrictor effect of ergotamine. 2 Treatment involves discontinuation of ergot medication and, in severe cases, the use of vasodilators, including prostaglandin E or methylprednisolone as second-line therapy.…”
Section: Discussionmentioning
confidence: 50%
“…Carotid involvement is uncommon but it has been described. 5 Septicemia, as in the case reported, can increase the vasoconstrictor effect of ergotamine. 2 Treatment involves discontinuation of ergot medication and, in severe cases, the use of vasodilators, including prostaglandin E or methylprednisolone as second-line therapy.…”
Section: Discussionmentioning
confidence: 50%
“…The patient became asymptomatic after a week. (Gaye-Saavedra et al, 2016) The cases reported for Ergot are presented in detail in Table 1, as below;…”
Section: Ergotamine Overdose Develops Cerebral Ergotismmentioning
confidence: 99%